Matematização: um outro estudo - Banheza, Karen Vanessa Gozer (2022)
In the last decades, the approach to the teaching of Mathematics, which emerged in the 1960s in the Netherlands, called Realistic Mathematics Education, has been studied and studied in Brazil. In the context of a Dutch school reform, Hans Freudenthal was the main researcher responsible for the ideas and pioneer of this approach in Mathematics Education. Among its fundamental characteristics is an idea of mathematization and an action of mathematizing. In order to carry out a study on mathematization within the scope of Realistic Mathematics Education, this was idealized. Thus, this master's dissertation in a report of this research, having a bibliographic and qualitative character, which proposes to investigate the term mathematization from the point of view of the author Hans Freudenthal through his articles and books. In addition to the study of mathematization, the aim is to corroborate the understanding of the origin of the term mathematization in the context of Realistic Mathematics Education. The research adopts an unconventional methodological procedure, inspired by the research methodology built in a doctoral thesis, in which an investigative study was carried out regarding a theory through logical processes. From the study and realization, we understand that Hans Freudenthal did not define a way of proceeding with the analysis, a step of how an apprentice can follow to carry out a mathematization. We realize that for him the activity of mathematization, mathematization, is an activity that occurs as a natural process, it must start from the reality of the individual, that is, understand what he calls mathematization, it is learning mathematics considering the reality of the individual. individual, through situations that lead the individual to his own mathematics, and not learn a ready-made, algorithmized mathematics. In addition, through the methodology used, it was possible to highlight that mathematization is presented in two ways: “Mathematization is an activity of a subject in reality”; and “Mathematization is a process possible for humans.”